THE EFFECT OF CYCLIC LOAD ON STEEL CANTILEVER - Epafroditus Tuwanakotta (LPPM Politeknik Saint Paul Sorong, 2017)
A steel cantilever beam given vertical load will be concentrated at the end of the vertical deformation. This study aims to analyze the bending strain and shear strain that occur in steel cantilever due to cyclic load and to find out the size of the load acting on the steel cantilever. The testing of cyclic load on steel cantilever was conducted by using SNI and ASCE 2005 references. The tests were conducted by using the laboratory physical model with desaign made by measuring the cantilever beam of 400.200.13.8 and a length of 1.060 meters. The end plate connection system was used for the connection of the cantilever beam. The were 12 bolts of high quality (A325) with a diameter of Ø 19 mm. The plate was 10 mm thick, and it had circumferential weld (70 Ksi and 8 mm thick) at the tip of the cantilever beam. The loading pattern was done repeatedly, and the compared with analytical calculation by using computer program numerical application. The test reveal that lateral load capacity increased along with the increase of displacement. The test of load and displacement controlled on the specimens reveal behaviors almost similar to elastic zone. The stiffness of the test specimen is relatively equal as the straight line coincides with the curve of the test specimen, and the strain occurring in the flange and web of the cantilever beam is still at the stage of elasticity. In the comparison between the analysis of SAP 200 and laboratory results, the difference is not really significant. When the load reaches 20 KN, the displacement is 1.988 mm in the analysis, 1.9890 in the sap 2000 calculation, and 1.8466 mm in the study.